Chronic toxicity of low dose monosodium glutamate in albino Wistar rats - Josiah Okwudili Nnadozie; Udunma Olive Chijioke; Okechukwu Charles Okafor; Daniel Bankole Olusina; Angus Nnamdi Oli; Patience Chiebonam Nwonu; Herbert Orji Mbagwu; Chioli Pascal Chijioke (BMC Research Notes, 2019)
Abstract Objective The objective of this study was to observe the effects of chronic dosing with monosodium glutamate on mortality, fertility, major organ functions and histology in albino Wistar rats. Results 6 male and 6 female rats (age 6 weeks) were bred in a cage, feeding on standard growers’ mash, with monosodium glutamate added (120 mg/kg/day). 12 corresponding breeding rats (on standard feed without MSG) were controls. Chronic dosing with monosodium glutamate in albino Wistar rats (at a dose consistent with the human ADI) led to increased mortality, fertility impairment, and significant changes in major organ function tests and histology. 23 deaths were recorded in the rats fed with MSG additive, while mortality was zero in the control animals. Fertility was lower in rats on MSG (48 births) than in controls (117 births). The weight gain of the MSG rats was higher than in controls. Biochemical parameters and organ histology remained normal in control animals. In MSG-treated rats however, liver/renal function tests, fasting serum cholesterol and triglyceride, serum uric acid showed a significant rise at trimestrial time-points. Histology showed mild portal inflammation in MSG rats, with periglomerular fibrosis and interstitial nephritis in two rats, at 6–12 months.